Evidence-based Practice of Pain Management in Postoperative Patients with Gastric Cancer - Wang Xicheng; Xiao Fang (American Journal of Nursing Science, 2026)
Objective: To construct an evidence based practice protocol for pain management in patients following gastric cancer surgery and evaluate its clinical application effects. Methods: Evidence-based nursing methods were employed to systematically retrieve, evaluate, and summarize evidence regarding post-gastric surgery pain management. Patient outcomes were compared before (June-September 2025, n = 70) and after (October-December 2025, n = 70) protocol implementation, alongside an evaluation of implementation processes among 28 on-duty nurses. Results: A total of 17 articles were included, yielding 10 pieces of best evidence across four themes: organizational and system management, pain screening and assessment, pain intervention, and health education and training. Post-implementation, patients' pain scores at 48–72 h postoperatively decreased from (3.61 ± 1.82) to (2.09 ± 2.16) points. Concurrently, patients' scores for pain control knowledge and analgesia self-management behaviors increased from (22.62 ± 4.42) to (29.69 ± 3.36) points and from (27.37 ± 6.53) to (38.71 ± 4.49) points, respectively. Furthermore, nurses' knowledge and attitude scores regarding pain management increased from (19.43 ± 5.06) to (29.82 ± 6.74) points. Conclusion: Implementing an evidence-based pain management protocol effectively enhances nurses' professional competence, optimizes ward pain management workflows, empowers patient self-management, and ameliorates postoperative pain outcomes.